Managemen Kepala Sekolah Dalam Peningkatan Kinerja Guru - Salim, Agus; Tanjung, Jihad; Awaluddin, Awaluddin (Yayasan Rahmat Islamiyah, 2023)
The purpose of this writing is to illustrate the management of efforts to improve teacher performance which is declining, such as: 1) Inaccuracy in attendance, 2) Unprofessional performance and so on. This phenomenon indirectly affects teaching and learning activities (KBM) in schools, which results in student learning achievement decreasing due to teachers being less professional. This will of course affect the quality of education and impact the good name of school institutions. When this has become a phenomenon, a system must be implemented to overcome this problem. And the main device subject is the school principal as a control device to evaluate and research the causes of this phenomenon. School principals must be discerning and intelligent in researching problems in depth and detail and finding solutions so that teacher performance problems can be resolved well, so that teachers as educators can restore their performance spirit to be more responsible and professional.